Perlindungan Hukum Terhadap Hak Pengembangan Diri Anak Akibat Dispensasi Perkawinan - Sulastri, Sulastri; Ramadhani, Dwi Aryanti; Sakti, Muthia (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
Researchers will examine the legal protection of the rights of children who enter into underage marriages. The purpose of this study is to show the impact of the ease of granting marital dispensation on children's development rights, namely how the legal protection of children's self-development rights is due to marital dispensation. The type of research used is normative legal research. The research approach used is the statutory approach and the comparative approach. The type of data in normative research is secondary data obtained through library research or documentation studies. Based on the results of the research, it turns out that there are still many parents who apply for marriage dispensation for children who are underage so they can get married. Therefore it is necessary to take action as an effort to provide legal protection to children. First, the government needs to review the Marriage Law, namely the need to add an article that regulates in detail the reasons for applying for a marriage dispensation. Second, it is necessary for the community to gain an understanding of the bad consequences that arise from underage marriages based on marriage dispensation.